2015
DOI: 10.3389/fmicb.2015.00929
|View full text |Cite
|
Sign up to set email alerts
|

Extensive in silico analysis of Mimivirus coded Rab GTPase homolog suggests a possible role in virion membrane biogenesis

Abstract: Rab GTPases are the key regulators of intracellular membrane trafficking in eukaryotes. Many viruses and intracellular bacterial pathogens have evolved to hijack the host Rab GTPase functions, mainly through activators and effector proteins, for their benefit. Acanthamoeba polyphaga mimivirus (APMV) is one of the largest viruses and belongs to the monophyletic clade of nucleo-cytoplasmic large DNA viruses (NCLDV). The inner membrane lining is integral to the APMV virion structure. APMV assembly involves extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Recently, a novel isoform of Rab5D was identified in the Acanthamoeba polyphaga mimivirus (APMV) and all group I members of the family Mimiviridae (29). Phylogenetic analyses suggested that the Rab GTPase was acquired by an ancestor of the Mimiviridae family, and Rabs from Mimiviridae, Plasmodium, and few lower eukaryotes form a separate clade (29). Thus, Legionella and APMV that both infect the protozoa Acanthamoeba encode Rab proteins, most likely to mimic and subvert host cell function.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel isoform of Rab5D was identified in the Acanthamoeba polyphaga mimivirus (APMV) and all group I members of the family Mimiviridae (29). Phylogenetic analyses suggested that the Rab GTPase was acquired by an ancestor of the Mimiviridae family, and Rabs from Mimiviridae, Plasmodium, and few lower eukaryotes form a separate clade (29). Thus, Legionella and APMV that both infect the protozoa Acanthamoeba encode Rab proteins, most likely to mimic and subvert host cell function.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies indicated the apparent monophyly of AVs ( Yutin and Koonin 2012 ; Zade, Sengupta, and Kondabagil 2015 ) and recent comparative genomics of diverse AVs have provided more robust phylogenies suggesting a probable lineage-specific expansion in AVs ( Iyer et al 2006 ; FilĂ©e 2009 ). Tracing the genome size over a phylogeny based on the B family DNA polymerase amino acid sequence, conserved across NCLDVs suggests the presence of larger genomes in the AV lineages ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of HGT-derived genes and MGEs ( Filee, Siguier, and Chandler 2007 ) has been used as evidence for the former argument, the presence of some translation-related genes and lack of cellular homologs of giant viral genes ( Jeudy et al 2012 ; AbrahĂŁo et al 2017 ) have been used to support the later. Genes related to key processes such as transcription, nucleotide metabolism, translation, virion assembly, and DNA packaging, are part of the Nucleo-Cytoplasmic Virus Orthologous Genes (NCVOGs) ( Yutin et al 2009 ) and are believed to be vertically transferred from a common ancestor ( Raoult et al 2004 ; Iyer et al 2005 , 2006 ; Chelikani et al 2014 ; Zade, Sengupta, and Kondabagil 2015 ). Isolation of several novel NCLDVs and their genomic characterization has reduced the number of conserved genes to nine ( Iyer, Aravind, and Koonin 2001 ; Yutin et al 2009 ), with a conceivable diversity in other core genes arising from replacement of essential genes by unrelated ones with similar function ( Forterre 2006 ; Iyer et al, 2006 ; Filee, Pouget and Chandler 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, silencing Rab5 or expressing the dominant negative mutant Rab5S34N significantly decreases foot-and-mouth disease virus infection ( Johns et al, 2009 ). Acanthamoeba polyphaga mimivirus even encodes a putative Rab5 homolog to recruit vps34, Atg-8 and dynamin for virus replication and particle assembly ( Zade et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%